Enhancing EFL Students Speaking Skills Through Digital Storytelling: A Case Study in a Vocational High School - Abdul Faliq Habbi Nawa; Sumartaevi Karlina Ambarwati (LINGUISTICA, 2025)
Digital storytelling (DST) has emerged as a powerful pedagogical tool in enhancing students’ speaking abilities, particularly in English as a Foreign Language (EFL) contexts. This study explores the implementation of DST in a vocational high school in Cianjur, Indonesia, using a qualitative case study approach. Data were collected through classroom observations and interviews with students to examine how DST influences their narrative speaking skills. The findings revealed that DST engages students actively through multimedia elements, improves their pronunciation and fluency, and boosts their speaking confidence. However, the study also identifies key challenges, including limited English proficiency, lack of confidence, and inadequate school facilities. The results indicate that while DST has strong potential in language learning, its success heavily depends on students’ foundational English skills and the availability of supporting infrastructure. The study concludes with suggestions for improving DST implementation in EFL classrooms, including increased training, better access to digital tools, and targeted support for speaking proficiency.